The role of research and development in increasing the competitive performance of petroleum companies: A case study of Royal Dutch Shell PLC - Elhousseyn, Benguettaia; Abbas, Bouhoreira (The International tax journal, 2025)
This study aims to highlight the role of research and development in enhancing the competitive performance of companies operating in the refining and petroleum industry in the face of competition from other firms in the same sector. This will be achieved by examining the relationship between research and development expenditure, market share and competitive performance through a case study of the multinational oil company Royal Dutch Shell PLC, considered one of the transnational companies, during the period from 2005 to 2021. Accordingly, this study will analyse competitive performance using a descriptive approach, analysing data through simple linear regression to determine the relationship between research and development expenditure and competitive performance. The study concluded that, despite maintaining its market position, research and development have a limited role in increasing the company’s competitiveness. Therefore, improving the quality of petroleum products and controlling production costs is suggested as a means of achieving better competitiveness.